Business incubators as drivers of innovation: Implications for investment and privatization initiatives within Saudi sports clubs - Selim, Hossam S.; Hassan, Ahmed K.; abualmakarem, Saeed M; Alsubaie, Sheikha Ammash; Aljamaan, Nahla Saad (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the role of business incubators as pivotal drivers of innovation within the context of Saudi sports clubs, particularly in light of recent investment and privatization initiatives. As the landscape of sports management transforms, Saudi Arabia has begun embracing a more privatized approach to sports club operations, encouraging private entrepreneurs to invest in this burgeoning sector. This paper examines the challenges faced by small- and medium-sized sports clubs, including high failure rates, within a competitive and rapidly evolving market. It argues that establishing business incubators can mitigate risks and offer a supportive environment for new and existing sports clubs to innovate and thrive. By fostering a knowledge-based, innovation-oriented culture, the research emphasizes the necessity of strategic investment in business incubators to ensure the sustainability and growth of sports organizations in a dynamic economic landscape. Furthermore, the implications for stakeholders within the sports industry and recommendations for the effective implementation of incubators are discussed.